DAMPAK PEMBERIAN BANTUAN MODAL USAHA TERHADAP PENINGKATAN PENDAPATAN KELOMPOK USAHA BERSAMA DI KABUPATEN RAJA AMPAT - , Daniel Goram, S.Sos. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The collective Business Group is an approach model exerted as a stimulant for the productive economy business group to increase their income and wealthy of the poor people. The research was made to measure the effectiveness on how the capital provided to the business group can influence the increase the collective business groupâs income in Raja Ampat district. To collect the data the writer applied a few methods and approaches such as deductive, quantitative, and positivistic in a way that conducting hypothesis to 70 respondents of the the business group receiving the money as the capital. The researchers met the group in the field conducting interview ,implementing survey, disseminating questionnaires, and conducting direct and indirect notes. The data analysis and clarification was executed by using the descriptive- analytic theory, examining the average results with 5 percent validity. Hence we can have the valid analysis of the every variable proving the income increase before and after the group obtaining the capital.